2000
DOI: 10.1007/s005350070065
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus in corticosteroid-resistant ulcerative colitis

Abstract: We report a case of refractory ulcerative colitis treated with tacrolimus. The patient was a 73-year-old woman with a 45-year history of ulcerative colitis. An attack unresponsive to intravenous corticosteroid therapy occurred when she was age 73. Leukocytapheresis therapy was attempted, but was discontinued because of the patient's poor general condition. Cyclosporine A therapy brought about fair control of the disease. A liver injury that was suspected to be associated with this agent, however, occurred with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…Since the fi rst suggestion that tacrolimus might be used to treat liver transplant recipients with IBD, 13 several case reports and uncontrolled trials have demonstrated the effi cacy of tacrolimus treatment in patients with CD and ulcerative colitis (UC). 8,11,[14][15][16][17] Our study is the fi rst to explore the effi cacy and safety of tacrolimus treatment in Japanese patients with CD and confi rms previous reports in other populations.…”
Section: Discussionsupporting
confidence: 77%
“…Since the fi rst suggestion that tacrolimus might be used to treat liver transplant recipients with IBD, 13 several case reports and uncontrolled trials have demonstrated the effi cacy of tacrolimus treatment in patients with CD and ulcerative colitis (UC). 8,11,[14][15][16][17] Our study is the fi rst to explore the effi cacy and safety of tacrolimus treatment in Japanese patients with CD and confi rms previous reports in other populations.…”
Section: Discussionsupporting
confidence: 77%
“…Standard drug formulations applied in the clinical studies with FK506 (Fellermann et al, 1998;Matsuhashi et al, 2000) released the drug during the intestinal passage followed by its systemic absorption. After oral administration, the effective dose of FK506 is lowered distinctly due to drug's P-gp-related efflux combined with inactivation from mucosal metabolism by CYP3A, which cause a relatively low bioavailability (Kagayama et al, 1993;Shimomura et al, 2002), subsequently reducing the therapeutic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low-molecular weight immune-suppressant drugs may still be of interest, however, requiring the design of intelligent drug delivery systems providing a more local treatment. FK506 (tacrolimus), initially developed as an immune-suppressive drug used to inhibit transplantation rejection, was successfully applied in IBD to treat refractory ulcerative colitis where corticoid treatment failed (Hoshino et al, 1995;Aiko et al, 1997;Fellermann et al, 1998;Matsuhashi et al, 2000). These treatments were based on oral FK506 administration with macroscopic carriers (tablets, etc.)…”
mentioning
confidence: 99%
“…Encouraged by positive effects of tacrolimus in sclerosing cholangitis (PSC) liver transplant recipients on their associated ulcerative colitis [ 19,20 ] anecdotal reports and case series of its use in autoimmune enteropathy [ 21 ] and inflammatory bowel disease followed [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%